2009
DOI: 10.1088/0004-637x/701/2/2019
|View full text |Cite
|
Sign up to set email alerts
|

ABUNDANT CIRCUMSTELLAR SILICA DUST AND SiO GAS CREATED BY A GIANT HYPERVELOCITY COLLISION IN THE ∼12 MYR HD172555 SYSTEM

Abstract: The fine dust detected by infrared (IR) emission around the nearby β Pic analog star HD172555 is very peculiar. The dust mineralogy is composed primarily of highly refractory, nonequilibrium materials, with approximately three quarters of the Si atoms in silica (SiO 2 ) species. Tektite and obsidian lab thermal emission spectra (nonequilibrium glassy silicas found in impact and magmatic systems) are required to fit the data. The best-fit model size distribution for the observed fine dust is dn/da = a −3.95±0.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
168
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(172 citation statements)
references
References 70 publications
(151 reference statements)
4
168
0
Order By: Relevance
“…While IR photometry of the system has remained stable since the 1983 IRAS mission, this steep size distribution, with abundant micron-sized particles, argues for a fresh source of material within the last 0.1 Myr (Lisse et al 2009;Johnson et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…While IR photometry of the system has remained stable since the 1983 IRAS mission, this steep size distribution, with abundant micron-sized particles, argues for a fresh source of material within the last 0.1 Myr (Lisse et al 2009;Johnson et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Unlike most young debris disks, and debris disks in general, the dust surrounding the primary star of HD 172555 is peculiar. Lisse et al (2009) took Spitzer/IRS spectra with λ/Δλ=90, covering wavelengths λ=5-35 μm and combined these results with additional IR photometry to determine the spectral energy distribution from 5 to 100 μm. They showed that a large amount of fine dust with a temperature of 245 K was at 5.8 ± 0.6 au from the primary (Lisse et al 2007), consistent with the later measurements of Pantin &di Folco (2011) using "Lucky Imaging," andSmith et al (2012) using Very Large Telescope (VLT)/MIDI interferometry that showed that the circumstellar dust emission arises from an axisymmetric torus of radius 1-8 au (Smith et al 2012) (0 2 at 29.3 pc).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations